ANALISIS LOCATION QUOTIENT (LQ) LAPANGAN USAHA PRODUK DOMESTIK REGIONAL BRUTO - Marthen A I Nahumury; Muhammad Abdullah Tawakal (Faculty Of Economics and Business, Musamus University, 2019)
This research aims to see the flagship sector or the base sector in Merauke Regency. The type of data in this research is the data that is made from the central body statistic the District of Merauke with a time period 2016-2018. The method used in this study is the Location Quotient (LQ) which is often used to see the development of the base sector in an area with the criteria LQ > 1 = base sector, LQ < 1 = Not a superior sector and if LQ = 1 Then the sector is only able to Meet the needs of its own region. The results of this study were obtained, almost all the business sector in Merauke District is a base sector. Where there are 3 sectors that are with the average value of LQ for the last three years, government administration, defence and social Security mandatory 0.04, Real Estate 0.97, as well as mining and excavation with LQ of 0.04 that is not a base sector. While 17 of the total sectors of 14 of them are the basis sectors where the results of the LQ showed that the agriculture, forestry, and fisheries sectors are still very superior to the average LQ 2.10 It is undeniable that the district Merauke is one of the largest rice suppliers for the surrounding area, such as Asmat District, Mappi and some other areas even the intereste state of Papua New Guinea.p Keywords: Featured sector, Location Quotient